Macro determinants and local effects of the informal labour in Colombia - García Cruz, Gustavo Adolfo (Sociedad y Economía, 2011)
This document studies the macroeconomics determinants of the informal labour in Colombia. By using several definition of informality the results show that the informality is related negatively with the education of the working population and the degree of industrially developed of the cities. The results also show that a big public sector has a positive effect on the informality, this indicate that public sector is not efficient or it has problems institutional that affect the decision of formalization. Furthermore, there is an important local effect related with the productive structure and commercial integration, which depends of the geographical localization of the cities.